EFFECT OF TIGERNUT (Cyprus esculentus.L) ADDITIVE ON GROWTH AND MILT QUALITY OF MALE AFRICAN MUD CAT FISH (Clarias gariepinus) - TUSAYI, B.W; ONYIA, L.U.; ISHAKU, R. (Nigerian Journal of Fisheries, 2021)
Fingerling production has faced a lot of challenges and plants/herbs are used as natural additives in animal diets to enhance reproductive performance. The study investigates the effect of Cyprus esculentus additive on the growth and milt qualities of male Clarias gariepinus. Feed was formulated at 35% CP and divided into five treatments based on the inclusion level of Tiger nut. Sixty adult catfish (C. gariepinus) with a weight between 595 ± 25.00 g and 600 ± 17.30 g were used. The fish were assigned to 12 per treatment and shared into 3 replicates in a concrete pond of size 1m by 1m by 1m. Mean Final Weight, Mean Final Weight Gain, Daily Growth rate, and survival ratio increase with an increase in the quantity of C. esculentus additive and shows a significant difference (p<0.05) within the treatment. Specific weight gain, Feed Conversion Ratio shows no significant difference (p>0.05) within the treatment but increases with increase in the quantity of C. esculentus additive. The result showed a significant difference (p<0.05) within the treatment in the Weight of the Right Lobe, Length of Right and Left Lobe, Milt volume, Milt count, and Milt motility were lowest in T1(Control) but increase with increased additive level of C. esculentus showed a significant difference (p<0.05). The weight of the Left Lobe shows no significant difference (p>0.05) within the treatment. This research shows C. esculentus can be used as an additive to boost growth and milt quantity in Clarias gariepinus.